Development of UNO STACKO Learning Media in Economics Subjects at State Senior High School 1 Aceh Barat Daya - Nana Suraiya; Amiruddin Amiruddin; A Razak; Miranda Pertiwi (Proceedings of AICS - Social Sciences, 2021)
The development of learning media is essential to improve students’ learning interest and motivation. The current study aimed at investigating the development and the feasibility of UNO STACKO learning media in economics subjects at State Senior High School 1 Aceh Barat Daya, Indonesia. It also investigates the response of teachers and students of the school after using uno stacko learning media in the teaching and learning process. This study used Research and Development (RD) approach using the ADDIE model. The study engaged 31 students and one teacher of economics subject. Data collection techniques are carried out by observation, documentation, and questionnaires. The results showed (1) the development of uno stacko learning media is worth testing at the school with material employment; (2) the feasibility level of uno stacko learning media in economics subjects is acknowledged very feasible with an average percentage of 85% with a very decent category; and (3) the response of teachers and students to the learning media of uno stacko showed very feasible, judging from the questionnaire of teacher and student responses with percentages of 81.66% and 89.87% respectively.Keywords: Uno stacko, learning media, economics subject, and student.